1913 Wyo. Sess. Laws 165, ch. 121, § 38 - (:unkn) unknown (General Publisher, 1913)
Required nonresidents obtain a license for $5 from the Justice of the Peace in order to hunt game birds in the state.
--
Keywords: HUNTING REGULATION